Potential Use of Forage Mixtures for Soil and Water Conservation, Agricultural Sustainability, and Climate Change Adaptation in Northern and Central West Tunisia - Souissi, Asma; Dhehibi, Boubaker; Frija, Aymen; M. Oumer, Ali; Idoudi, Zied; M'hamed, Hatem Cheikh; Ben Youssef, Salah; Bahri, Haithem; Le, Quang Bao; Shiri, Zahra; Wafa, Ameur; Ouerghemmi, Hassen; et al. (International Center for Agricultural Research in the Dry Areas, 2023)
This policy brief provides empirical evidence on the profitability of soil and water conservation (SWC) practices and forage mixtures, implemented to mitigate soil erosion and land degradation in Northern and Central West Tunisia.